Qualidade das águas da Bacia Hidrográfica do Córrego Góis Anápolis/GO - MACHADO, Eduardo Vieira (2009)
The city of Anapolis / GO has an approximate area of 140 km ², representing 15% of the total area of the municipality, which covers 918 km ². The city located 57 kilometers from Goiânia and 160 km from Brasília, the call Mesoregião Center Goiano, its population is approximately 326 thousand inhabitants. The research direction was to the urban area of Anapolis, specifically in the basin of the stream Góis, which is inserted fully within the boundaries of the city. Located in the southern portion, Góis of the basin covers an area of approximately 11.18 km2. About 25% of the whole area of the basin is covered by forests and pasture. The Stream Góis crosses thirty-two neighborhood in the city center and converge with the stream of Antas, its main tributary is a stream of water eyes. The basin consists of mainly residential buildings, but in the neighborhoods that border the BR-060 and Avenue Brazil South, there are several machanical workshops, however there are other types of economic activities such as trade and regional services for medium and large. By the end of 2007 the resident population in the basin was approximately 37,842 inhabitants. The assessment done to check the water quality of the stream Góis were based on ten different physico-chemical parameters, to determine its relationship with the use and occupation of land. The collections of water occurred in February and September 2007, were selected for this four points within the perimeter of the basin, the criteria for selection of these points were: Possible environmental degradation, forms of use and occupation, effluents and tributaries. The results indicated a somewhat severe contamination in 1 and 2 and more pronounced in 3 and 4. Stream Góis is based, according to CONAMA Resolution 357/05, in Class II.